PENGARUH NILAI-NILAI ISLAM TERHADAP PENGUNGKAPAN SUKARELA TATA KELOLA PERUSAHAAN (Studi kasus pada perusahaan yang tercatat di JII 2016-2017) - Muhamad Wildan Nur Hidayat; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2019)
Corporate governance is an important for every company. There are many factor that influence voluntary corporate governance disclosure. This research examines the effect Islam values disclosure on voluntary corporate governance disclosure. In particular, this study examines whether companies that incorporate and disclose Islamic values in their business operations can explain the different levels of voluntary corporate governance disclosure.The data used as objects in this study are companies that have been registered at the Jakarta Islamic Index (JII) in 2016-2017 consisting of 76 data that were used as objects in this study, namely companies that have registered at the Jakarta Islamic Index (JII) in 2016-2017 which consists of 38 companies. This study uses a simple linear regression analysis method because it only has one dependent variable measured using the Corporate Governance Index (CGI) and one independent variable measured using the Islamic Values Disclosure Index (IVDI).From the results of this study it was found that disclosure of Islamic values had a positive effect on voluntary corporate governance disclosure. The higher the disclosure of Islamic values index score engage in higher the voluntary corporate governance disclosure index score.